Fossils know it best: Using a new set of fossil calibrations to improve the temporal phylogenetic framework of murid rodents (Rodentia: Muridae) - Aghová, Tatiana; Kimura, Yuri; Bryja, Josef; Dobigny, Gauthier; Granjon, Laurent; Kergoat, Gael J (Molecular phylogenetics and evolution, 2018)
Murid rodents (Rodentia: Muridae) represent the most diverse and abundant mammalian family. In this study, we provide a refined set of fossil calibrations which is used to reconstruct a dated phylogeny of the family using a multilocus dataset (six nuclear and nine mitochondrial gene fragments) encompassing 161 species representing 82 murid genera from four extant subfamilies (Deomyinae, Gerbillinae, Lophiomyinae and Murinae). In comparison with previous studies on murid or muroid rodents, our work stands out for the implementation of nine robust fossil constraints within the Muridae thanks to a thorough review of the fossil record. Before being assigned to specific nodes of the phylogeny, all potential fossil constraints were carefully assessed; they were also subjected to several cross-validation analyses. The resulting phylogeny is consistent with previous phylogenetic studies on murids, and recovers the monophyly of all sampled murid subfamilies and tribes. Based on nine controlled fossil calibrations, our inferred temporal timeframe indicates that the murid family likely originated in the course of the Early Miocene, 22.0-17.0 million years ago (Ma), and that most major lineages (i.e. tribes) started diversifying ca. 10 Ma. Historical biogeography analyses support the tropical origin for the family, with an initial internal split (vicariance event) between Afrotropical and Oriental (Indomalaya and Philippines) lineages. During the course of their diversification, the biogeographic pattern of murids is marked by several dispersal events toward the Australasian and the Palearctic regions. The Afrotropical region was also secondarily colonized at least three times from the Indomalaya, indicating that the latter region has acted as a major centre of diversification for the family.
Keywords: Bayes Theorem; Animals; Fossils; Phylogeny; kalibrace; Phylogeography; zkameněliny; Time Factors; Muridae; fylogeneze; fylogeografie; časové faktory; Calibration; Bayesova věta; zvířata